2016
DOI: 10.1002/mrm.26383
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Shift magnetization transfer magnetic resonance imaging

Abstract: Purpose To develop a chemical shift magnetization transfer (CSMT) MRI method to provide accurate MTR measurements in the presence of fat. Methods Numerical simulations were performed to compare MTR measurements at different echo-times (TEs) for voxels with varying fat/water content. The CSMT approach was developed using water fraction estimates to correct for the impact of fat signal upon observed MTR measurements. CSMT method was validated with oil/agarose phantom and animal studies. Results Simulations d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…20,49,50 However, fat-suppression and water-or fat-selective pulses may cause additional MT effects and/or alter the steady state of MT sequences. 48 Because the measured PDFF values in this study correlate well with histopathologic grading of the pancreatic lipomatosis, it can be assumed that the applied chemical shift-based multiecho gradient imaging sequence for fat quantification actually measures the fat deposition in the pancreas. Also the MTR measurements in the subcutaneous fat show good agreement with published data with MTR close to zero.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…20,49,50 However, fat-suppression and water-or fat-selective pulses may cause additional MT effects and/or alter the steady state of MT sequences. 48 Because the measured PDFF values in this study correlate well with histopathologic grading of the pancreatic lipomatosis, it can be assumed that the applied chemical shift-based multiecho gradient imaging sequence for fat quantification actually measures the fat deposition in the pancreas. Also the MTR measurements in the subcutaneous fat show good agreement with published data with MTR close to zero.…”
Section: Discussionmentioning
confidence: 67%
“…Fat deposition in soft tissue environment has a confounding effect on MTR values. 17,18,20,48 The MT effect grows with the number of hydrogen nuclei that switch from a high-mobility environment, such as in a free water molecule, to a low-mobility environment, such as, for example, in a hydroxyl group bound to a macromolecule. 17 The free water proton pool is diminished in a fatty environment and therefore the measured MTR are reduced.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of fat to the ihMT signal has not previously been investigated. Previous studies of MT, 11,24 CEST, 25 and quantitative MT 26 imaging showed evidence of variation on MTR, MTR asym , and quantitative MT values, depending on the fat fraction in the corresponding voxel. While similar to ihMT, these sequences rely on different chemical or physical principles and use different postprocessing, thus demonstrating salient differences with respect to the influence of fat.…”
Section: Discussionmentioning
confidence: 92%
“…The IhMT applications outside of the central nervous system would involve imaging in close proximity to adipose tissue (which is found near nerves and muscles) and may be further complicated by infiltration into the surrounding fat by different pathologies 10 . The presence of fat is known to create chemical shift artifacts and compromise tissue characterization 11‐13 . Moreover, neuroradiological studies of the head and neck routinely use fat‐suppression methods that improve visualization of pathology 14‐16 .…”
Section: Introductionmentioning
confidence: 99%
“…This increased cellular lipid content may additionally be accountable for a further reduction of magnetization transfer. [ 32 ]. Thus, either a potentially elevated cellular hypertrophy or a higher number of proliferating, hence swollen hepatocytes, or both, together with a possibly enhanced lipid content might eventually account for the rather pronounced decline in MTR after ePH as compared to cPH.…”
Section: Discussionmentioning
confidence: 99%